Pengaruh Tayangan Vlog Ekspedisi “Langit Kelabu” Terhadap Sikap Gen Z Akan Hal Mistis - Erlangga Fajri Ramadanny; Eugenius Kau Suni (SABER : Jurnal Teknik Informatika, Sains dan Ilmu Komunikasi, 2024)
The concept of the mystical in society embodies an air of mystery, fear, suspense, horror, and the like, leading the inability of society to understand mystical phenomena to drive a high level of curiosity about such occurrences. Even the mystical has become a form of entertainment for society, one of which is through consuming horror content on YouTube. In the present era, Generation Z is a cohort whose lives have evolved with distinct thought patterns compared to preceding generations, parallel to the relentless development of the digital technology world. One manifestation of internet content or YouTube content is the "Langit Kelabu" expedition vlog, which explores mystical mountain climbing expeditions. The content is produced and hosted by a creator named Dzawin Nur Ikram on the YouTube channel "Dzawin Nur." This study aims to ascertain the influence and the extent of impact by the "Langit Kelabu" vlog on the Dzawin Nur YouTube channel on the attitudes of Generation Z toward the mystical. This is approached quantitatively through an explanatory survey method and utilizes purposive sampling for sample collection. The study employs the S-O-R Theory as the overarching research framework. The findings indicate a 44.3% influence of the "Langit Kelabu" YouTube vlog on the attitudes of Generation Z toward mystical phenomena. The conclusion of this study is the presence of a significant or strong correlation coefficient between the "Langit Kelabu" Expedition Vlog and the attitudes of Generation Z towards mysticism, as indicated by the coefficient of determination test results, which also show that there is a moderate level of influence from the "Langit Kelabu" YouTube vlog on the attitudes of Generation Z towards mystical phenomena.